Pengaruh Laba Bersih, Arus Kas Operasi, Arus Kas Investasi, Dan Arus Kas Pendanaan Terhadap Harga Saham (Studi Pada Perusahaan Sektor Pertanian Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2020) - Fabiola Kharisma Fitrian Desinta; Lis Lestari Sukartiningsih (Universitas Katolik Widya Karya Malang, 2022)
The purpose of this study was to determine the effect of net income, operating cash flow, investment cash flow, and funding cash flow on stock prices in agricultural sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period. This type of research is explanatory research. The study population was 29 companies, the sample selection used a purposive sampling technique, 7 companies were selected. The analysis technique uses descriptive statistical tests, classical assumption tests, multiple linear regression tests, and hypothesis testing. The results of the analysis simultaneously, the variable net income, operating cash flow, investment cash flow, and funding cash flow affect stock prices. Net profit, operating cash flow, investment cash flow and funding cash flow partially have no effect and are not significant to stock prices. There is no dominant variable on stock prices, because there are no variables that have a partial effect.